Creating two self-assembly micro-environments to achieve supercrystals with dual structures using polyhedral nanoparticles - Lee, Yih Hong (2018)
Organizing nanoparticles into supercrystals comprising multiple structures remains challenging. Here, we achieve one assembly with dual structures for Ag polyhedral building blocks, comprising truncated cubes, cuboctahedra, truncated octahedra, and octahedra. We create two micro-environments in a solvent evaporation-driven assembly system: one at the drying front and one at the air/water interface. Dynamic solvent flow concentrates the polyhedra at the drying front, generating hard particle behaviors and leading to morphology-dependent densest-packed bulk supercrystals. In addition, monolayers of nanoparticles adsorb at the air/liquid interface to minimize the air/liquid interfacial energy. Subsequent solvent evaporation gives rise to various structurally diverse dual-structure supercrystals. The topmost monolayers feature distinct open crystal structures with significantly lower packing densities than their densest-packed supercrystals. We further highlight a 3.3-fold synergistic enhancement of surface-enhanced Raman scattering efficiency arising from these dual-structure supercrystals as compared to a uniform one.